2021
DOI: 10.1111/eva.13276
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and corridors of gene flow in an urbanized tropical reef system

Abstract: Tropical coral reefs are in rapid decline due to climate change impacts and multiple local-scale stressors (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 147 publications
(172 reference statements)
0
16
0
Order By: Relevance
“…Based on the >10 m distance among colonies [46,47] and our molecular results, we assumed all five colonies represented distinct genotypes. Population genetics studies conducted to date in Singapore have not detected unambiguous clonality [48,49].…”
Section: Study Site Species and Sample Collectionmentioning
confidence: 94%
“…Based on the >10 m distance among colonies [46,47] and our molecular results, we assumed all five colonies represented distinct genotypes. Population genetics studies conducted to date in Singapore have not detected unambiguous clonality [48,49].…”
Section: Study Site Species and Sample Collectionmentioning
confidence: 94%
“…Reef connectivity is increasingly being considered in the design and establishment of marine protected areas (Beger et al, 2015; Magris et al, 2016; Crandall et al, 2019; but see Balbar & Metaxas, 2019). For example, when Singapore enacted its first coral‐reef marine park, authorities explicitly chose areas with both high reproductive potential and high genetic diversity (Afiq‐Rosli et al, 2021). Moreover, studies along the Australian Great Barrier Reef showed that a small fraction of reefs can serve both as potential thermal refugia and as ‘robust source reefs’ for a substantial portion of the reef network (Cheung et al, 2021; Hock et al, 2017).…”
Section: From Science To Management Actionmentioning
confidence: 99%
“…To date, most studies that examine genome-wide DNA polymorphisms in corals aim to determine population structure and genetic connectivity (Afiq-Rosli et al, 2021) while the structural and functional effects of these variants are rarely examined. Nevertheless, a few studies have highlighted genomic signatures of adaptation in corals to challenging conditions (Bay & Palumbi, 2014;Cooke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%